Technology transfer model for the formulation stage in biological products for public health - Jorge L Magalhães; Alessandra L Viçosa; Giselle Ribeiro de Barros (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Technology transfer is a tool used to absorb knowledge and technology, in addition to increasing a country's technological innovation. In the health sector, it is no different, especially in times of outbreaks, epidemics and global pandemic. Therefore, tools that assist in the creation of public policies contribute to the research, development and innovation of new technologies to produce vaccines and medicines. Thus, it proposes a universal technology transfer model based on International guides from the World Health Organization, Parenteral Drugs Association and the International Society of Pharmaceutical Engineering. It was concluded that the model ensures reliability between the parties and promotes a dynamic and rapid methodology for application in public health in the country.